2015
DOI: 10.1177/1747493015609778
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical thrombectomy in acute ischemic stroke: Consensus statement by ESO-Karolinska Stroke Update 2014/2015, supported by ESO, ESMINT, ESNR and EAN

Abstract: The original version of this consensus statement on mechanical thrombectomy was approved at the European Stroke Organisation (ESO)-Karolinska Stroke Update conference in Stockholm, 16-18 November 2014. The statement has later, during 2015, been updated with new clinical trials data in accordance with a decision made at the conference. Revisions have been made at a face-to-face meeting during the ESO Winter School in Berne in February, through email exchanges and the final version has then been approved by each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
227
1
15

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 327 publications
(250 citation statements)
references
References 59 publications
5
227
1
15
Order By: Relevance
“…This study could not provide further information on patients with NCCT ASPECTS of 0 -4 because of a paucity of data. 18 Therefore, there are not thorough data concerning the effects of ET in patients with larger infarct burdens, and we only know that those with lower ASPECTS could be unsuitable for ET 19 but cannot be excluded from treatment. A recent study of 249 patients showed a rate of good outcome of 5% in the CT ASPECTS group of 0 -4 and of 38.5% in the CT ASPECTS group of 5-8, 7 suggesting a chance for ET in patients with larger infarct burden.…”
Section: Discussionmentioning
confidence: 99%
“…This study could not provide further information on patients with NCCT ASPECTS of 0 -4 because of a paucity of data. 18 Therefore, there are not thorough data concerning the effects of ET in patients with larger infarct burdens, and we only know that those with lower ASPECTS could be unsuitable for ET 19 but cannot be excluded from treatment. A recent study of 249 patients showed a rate of good outcome of 5% in the CT ASPECTS group of 0 -4 and of 38.5% in the CT ASPECTS group of 5-8, 7 suggesting a chance for ET in patients with larger infarct burden.…”
Section: Discussionmentioning
confidence: 99%
“…The number needed to treat with endovascular thrombectomy to reduce disability by at least one level on the modified Rankin Scale (mRS) for one patient was 2·6, which is extraordinary in itself and a huge advance in care for patients with stroke caused by occlusion of the major intracranial carotidterritory vessels, who often respond poorly to optimal medical care with intravenous thrombolytic drugs 2 and have high risk of mortality or disability. Updates to European and North American guidelines [3][4][5] for acute stroke management have already reflected the findings of these trials by recommending endovascular thrombectomy in suitable patients, conclusions supported by the HERMES analysis.…”
Section: Hermes: Messenger For Stroke Interventional Treatmentmentioning
confidence: 91%
“…Since the publication of the results of the MR-CLEAN, ESCAPE, EXTEND, REVASCAT and SWIFT studies, thrombectomy is indicated and practiced in stroke centers in high income countries [11]. Its indications are well codified and require expertise, a multidisciplinary team and expensive equipment, which make it very difficult to access for patients in sub-Saharan Africa, as in Congo.…”
Section: Case Reportmentioning
confidence: 99%